Demonstration of Decolorization of Various Dyes by Some Bacterial Isolates Recovered from Textile Effluents - Mahbub, KR; Ferdouse, J; Anwar, MN (Bangladesh Journal of Scientific and Industrial Research, 2011)
In the present study some predominant bacteria from textile effluent were isolated and their decolorizing activity was evaluated. Heavy load of bacteria (1.3 × 103 to 3.07 × 107 cfu/ml) were found in eight effluent samples collected from two textile industries. Six dye decolorizing bacteria were isolated and identified as Bacillus fastidiosus, Bacillus polymyxa, Bacillus licheniformis, Bacillus megaterium, Staphylococcus aureus and Micrococcus luteus. The isolates were tested for their ability to decolorize different concentrations (0.01, 0.05 and 0.1%) of six different textile dyes. Among the dyes Terasil red W-FS and Terasil black W-NS were found to be completely decolorized by the all isolates at different concentrations. Cibacron yellow F-4G was decolorized very easily by B. fastidiosus while the other dyes were only partially decolorized by the test organisms. Cibacron blue FN-R, Cibacron navy FN-B and Cibacron orange FN-R were only weakly decolorized by the most of the isolates. The results of the present study show that B. fastidiosus, B. polymyxa, M. luteus and S. aureus were the potential isolates in the treatment of dyeing industry effluents and their potentiality can be exploited to clean up the environment. Key words: Bacteria; Effluent; Dye; Decolonization. DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9037 BJSIR 2011; 46(3): 323-328